Smart fiber with overprinted patterns to function as chip-like multi-threshold logic switch circuit - Xiaofei Wei; Rui Li; Siwei Xiang; Long Qin; Xinxin Luo; Jie Xue; Xing Fan (Nature Communications)
Abstract There is a growing demand for precise health management, capable of differentially caring every inch of skin as an on-body network. For which, each network node executes not only multi-physiological sensing, but also in-situ logic computing to save cloud computing power for massive data analysis. Herein, we present a smart fiber with multilayers of overprinted patterns, composed of many small units with 0.3 mm long to function as a one-dimension (1D) array of chip-like multi-threshold logic-switch circuit. Via soft contact of curved surfaces between fiber and ink-droplet, an overprinting method is developed for stacking different layers of patterns with a line width of 75 μm in a staggered way, enabling batch production of circuit units along one long fiber. A smart fiber with high density of >3000 circuit units per meter can be woven with fiber-type sensors to construct a textile-type body-covering network, where each node serves as a computing terminal.